The Phenomenological of Mamakiah Activities for Islamic Boarding School Students in Indonesia: What Are the Values and Goals? - Nursyda, Filda; Hidayati, Hidayati; Kartini, Fina (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
Mamakiah activities are an important aspect of santri education in traditional surau. Mamakiah is an activity for students to leave the mosque and go around the surrounding villages to ask alms from the community. Mamakiah's main goal is to meet the educational needs of underprivileged students, such as buying books and other learning equipment. In addition, mamakiah also provides opportunities for students to socialize with the surrounding community and add insight through direct interaction with the community. In the context of classic Islamic boarding schools in Indonesia, mamakiah activities are still carried out by santri. Unique activities certainly have certain values ​​and goals. This study aims to find out what the values ​​and goals of mamakiah activities are. The research method used is qualitative with a phenomenological approach. Sources of data were taken from five informants through in-depth interviews. The research findings show that there are four important aspects in mamakiah activities: i) bringing students and society closer together, ii) strengthening the character and toughness of students, iii) means of da'wah for students, iv) continuing the classical Islamic boarding school education system in a sustainable manner. The results of this study are expected to provide a better understanding of the role of mamakiah in the education of students as well as the social, religious, and skills values ​​that can be acquired through this activity.